Washable Multilayer Triboelectric Air Filter for Efficient Particulate Matter PM2.5 Removal. (5th February 2018) - Bai, Yu; Han, Chang Bao; He, Chuan; Gu, Guang Qin; Nie, Jin Hui; Shao, Jia Jia; Xiao, Tian Xiao; Deng, Chao Ran; Wang, Zhong Lin
Abstract: Efficient removal of particulate matter (PM) is the major goal for various air cleaning technologies due to its huge impact on human health. Here, a washable high‐efficiency triboelectric air filter (TAF) that can be used multiple times is presented. The TAF consists of five layers of the polytetrafluoroethylene (PTFE) and nylon fabrics. Compared with traditional electrostatic precipitator, which requires a high‐voltage power supply, the TAF can be charged by simply rubbing the PTFE and nylon fabrics against each other. The electrical properties of the TAF are evaluated through the periodic contacting–separating of the PTFE and nylon fabrics using a linear motor, and an open‐circuit voltage of 190 V is achieved. After charging, the TAF has a removal efficiency of 84.7% for PM0.5, 96.0% for PM2.5, which are 3.22 and 1.39 times as large as the uncharged one. Most importantly, after washing several times, the removal efficiency of the TAF maintains almost the same, while the commercial face mask drops to 70% of its original efficiency. Furthermore, the removal efficiency of the PM2.5 is very stable under high relative humidity. Therefore, the TAF is promising for fabricating a reusable and high‐efficiency face mask. Abstract : A multilayer triboelectric air filter consists of five layers of polytetrafluoroethylene (PTFE) and nylon fabrics. A high removal efficiency is achieved by rubbing the fabrics against each other, and the removal efficiency maintains high under high humidity, in a durability test or after several washing cycles. Moreover, a face mask made of this air filter can be used in daily life.